Electronic marketing : - Reedy, Joel (Thomson Learrning, 2004)
This text for marketing students combines traditional processes of marketing analysis, planning, and implementation, with a new focus on the enhanced speed and targeting ability of the Internet and other electronic resources. The text includes case studies of companies using electronic solutions to solve marketing and communication problems, and discussions of the advantages and disadvantages of doing business on the Internet. Chapter topics include segmenting and analyzing the target market, developing virtual storefronts, building successful websites, dealing with hackers, protecting customer privacy, and the value of repeat customers. New features in the second edition include a new preface, and a discussion of business-to-business use of the Internet.